Analysis of Implementation of Integrated Management of Sick Toddlers (MTBS) by Midwife - Anah Hidayati; Novita Novita (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
In order to reduce the Mortality and Illness Rate in Toddlers (angka kematian balita /AKABA) in Indonesia, the Government implements the Integrated Management of Sick Toddlers ( manajemen terpadu balita sakit / MTBS) strategy. However, the implementation of MTBS has not been effective. The purpose of this study was to analyze the implementation of MTBS at the location of midwife independent practice (PMB). This study was cross-sectional. The research location is in the working area of the Lebak Wangi Health Center from May to June 2023. The sample in this study was 30 midwives practice locations. Independent variables are facilities and infrastructure, midwives' education level about MTBS, midwives' age, and socialization of MTBS practices. The analysis to be used is multiple logistic regression with results in the form of aOR (adjusted odds ratio). The results of multivariate analysis on facilities and infrastructure factors that have a 3-fold influence on MTBS completeness and are statistically significant (aOR= 3.38; 95% CI= 1.34 to 646.9; p= 0.032 < 0.05) and MTBS socialization factors that have been followed by midwives also affect the completeness of MTBS up to 2.8 times compared to never getting MTBS socialization (aOR= 2.85; 95% CI= 1.15 to 257.6; p= 0.039 < 0.05).